Retracted Article: Resveratrol attenuates inflammation and reduces matrix-metalloprotease expression by inducing autophagy via suppressing the Wnt/β-catenin signaling pathway in IL-1β-induced osteoarthritis chondrocytes. Issue 36 (4th June 2018) - Li, Ci; Wu, Wenliang; Jiao, Guangjun; Chen, Yunzhen; Liu, Haichun
Abstract : Resveratrol (Res), a naturally occurring polyphenolic compound, has been reported to exert many biological effects like anti-inflammatory and anti-oxidant effects. Abstract : Resveratrol (Res), a naturally occurring polyphenolic compound, has been reported to exert many biological effects like anti-inflammatory and anti-oxidant effects. In this study, we investigated the role of Res on IL-1β-induced osteoarthritis (OA) chondrocytes and its possible mechanism. Results demonstrated that Res suppressed IL-1β-induced IL-1, IL-6 and TNF-α production in a dose-dependent manner. Res also decreased MMP-1, MMP-3 and MMP-13 production in IL-1β-induced OA chondrocytes. These results suggested that Res suppressed IL-1β-induced inflammation and matrix-metalloproteases (MMP) expression in OA chondrocytes. In addition, Res was found to reverse the decreased autophagy level through increasing the expression of Beclin1, LC3 II/I ratio and LC3 + puncta in IL-1β-induced OA chondrocytes. Inhibition of autophagy by 3-methyladenine (3-MA) abolished the inhibitory effect of Res on inflammation and MMP expression in IL-1β-induced OA chondrocytes. Moreover, the Wnt/β-catenin signaling pathway was activated in IL-1β-induced OA chondrocytes. However, Res was found to suppress this activated Wnt/β-catenin signaling pathway. Activation of the Wnt/β-catenin signaling pathway counteracted the promoted effect on autophagy and inhibitory effect on inflammation and MMP expression of Res in IL-1β-induced OA chondrocytes. Taken together, our data demonstrated that Res attenuated inflammation and reduced MMP expression through inducing autophagy via inhibiting the Wnt/β-catenin signaling pathway in IL-1β-induced OA chondrocytes. Res may be used as a potential therapeutic agent for OA treatment.